the archaeology of improvement in britain, 1750 -1850 - Tarlow, Sarah (Cambridge University Press, 2013)
This book is not a complete account of the history and archaeology of Britain between 1750 and 1850. The history books alone dealing with that century fill several hundred metres of shelf space in my university library and one obviously cannot distil all that information, or even the most important bits of it into one, medium-sized book. Instead I have chosen to focus on aspects of the material evidence of the period which throw light on what I consider to be an important and characteristic aspect of the period: the idea of Improvement. My (admittedly ambitious) aim here is to provide an enhanced historical and theoretical context for existing and future work; to complement and contextualise the numerous pieces of small scale and meticulous work that have been produced in industrial, post-medieval and landscape archaeology